9. THE IMPROVEMENT AND RICHNESS OF AURICULOTHERAPY IN TREATMENT OF INSOMNIA (Vietnam Journal of Community Medicine, 2024)
Research objective: To learn more deeply and more objectively evaluate the effects of ear acupuncture as well as develop new methods in combination with auriculotherapy in the treatment of chronic diseases. We summarize the research of internal and external authors water in recent years.Research methods: Literature review.Conclusion: The discovery, creation and combination of new methods of ear acupuncture in the treatment of insomnia in recent years have been of great significance in improving sleep for patients. The methods are both effective, safe, easy to perform, and highly effective. These are extremely wonderful advantages of ear acupuncture, contributing to enhancing the position of traditional medicine in people’s health care.
Keywords: Insomnia; auriculotherapy